(untitled) (Genitri: Jurnal Pengabdian Masyarakat Bidang Kesehatan, 2025)
School children’s health plays a vital role in supporting their growth, development, and learning achievement. One of the persistent environmental health problems in Bali, including Badung District, is the increasing incidence of dengue fever due to low public awareness of environmental sanitation. The activity employed a qualitative, participatory, and descriptive approach involving students, teachers, and school stakeholders. Activities included interactive health education on dengue, the 3M Plus practice (draining, covering, and recycling), demonstrations of simple mosquito traps, and classroom cleanliness competitions. Data were collected through interviews, observations, and group discussions. The results showed a significant improvement in students’ knowledge scores from 62% to 91%, accompanied by positive behavioural changes such as regularly cleaning stagnant water and maintaining environmental cleanliness. The school environment became cleaner and free from mosquito breeding sites. This programme proved effective in enhancing students’ awareness of clean and healthy living behaviour (CHLB) as an effort to prevent dengue transmission. It can serve as a sustainable school health promotion model involving the entire school community.